2015
DOI: 10.1002/ccr3.352
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a 46,XX male following noninvasive prenatal testing

Abstract: Key Clinical messageCase report involving a normal female by NIPT with male external genitalia on routine fetal morphology assessment. QF-PCR, CGH microarray, and FISH revealed an unbalanced translocation, involving the short arms of the X and Y chromosomes. This case demonstrates the possible limitations of correctly identifying sex chromosome abnormalities via NIPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Prenatal karyotyping was performed in 38 cases (65.5%) and postnatally in 9 cases. There were 11 cases (19.0%) without prenatal (1), and live birth with normal neonatal examinations (9). The two participants with dual aneuploidy high risk results made decisions regarding invasive prenatal testing based on the autosomal abnormality potential rather than the SCA and are not included in the SCA invasive testing results (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal karyotyping was performed in 38 cases (65.5%) and postnatally in 9 cases. There were 11 cases (19.0%) without prenatal (1), and live birth with normal neonatal examinations (9). The two participants with dual aneuploidy high risk results made decisions regarding invasive prenatal testing based on the autosomal abnormality potential rather than the SCA and are not included in the SCA invasive testing results (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…aCGH and fluorescence in situ hybridization testing revealed an unbalanced translocation involving the short arms of X and Y chromosomes, which included the SRY region (SRY-positive 46,XX testicular disorder of sexual development) [9].…”
Section: Casementioning
confidence: 99%
“…Variations in the traditional XX or XY fetal karyotype may result in conditions where the genotype is discordant with the phenotype (Richardson et al, ). Mansfield et al () reported diagnosis of a 46, XX male following NIPS. In this case, a 40‐year‐old woman underwent NIPS at 10 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The patient subsequently underwent an amniocentesis for cytogenetic testing that was consistent with Chromosomes X and partial Y, which contained the marker for SRY gene that is responsible for the initiation of male sex determination in humans. An unbalanced translocation was determined to be the cause for this discordance (Table ) (Mansfield et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, prenatally obtained fetal sex information can favor unethical sex selection, if not prohibited by legal obligations. Fourth, NIPT based fetal sex determination can potentially be discordant to ultrasound-or karyotype-based gender determination due to congenital adrenal hyperplasia [48], androgen insensitivity [49] or gonosomal translocations [50]. Apart from these confounding factors, several technical challenges with gonosomal sequencing result in suboptimal SCA-or fetal sex-detection.…”
Section: The Performance Of Niptmentioning
confidence: 99%